Unscarred uterine rupture: a retrospective analysis - Paidi, Sirisha; K., Bhavani; P. S., Prasanthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine rupture is an obstetrical emergency associated with significant maternal and fetal mortality and morbidity. Spontaneous rupture of an unscarred uterus, though rare, can occur in developing countries. Many risk factors for uterine rupture, as well as a wide range of clinical presentations, have been identified. The aim of the study was to analyze the incidence, predisposing factors and to determine the maternal and perinatal outcomes of unscarred uterine rupture. A retrospective analysis of cases of unscarred uterine rupture was conducted at the department of obstetrics and gynecology, Andhra Medical College/King George Hospital, Visakhapatnam from 01 October 2020 to 31 October 2021. Out of the 8657 deliveries in our hospital during the study period, there were 11 cases of ruptured unscarred uteri giving an incidence of 0.127%. All of these (100%) were unbooked cases. Most of them (90.9%) were multigravida. Uterine rupture occurred at term in 9 cases and 2 were pre term. Maternal mortality was 18.18% (2 cases) and perinatal mortality was 72.72% (8 cases). Sub-total hysterectomy was done in 4 and laparotomy with repair of the rent was performed in the remaining 7 cases. Unscarred uterine rupture though a rare complication of pregnancy, can occur commonly in developing countries. Obstructed labour, mismanaged labour, injudicious use of oxytocin and grand multiparity are the common risk factors associated with unscarred uterine rupture.